De-stressing plaques attenuates atherosclerosis progression. Issue 8 (August 2022) - Nettersheim, Felix Sebastian; Ley, Klaus
Abstract : Atherogenesis is accompanied by formation of immune cell aggregates, so-called artery tertiary lymphoid organs (ATLOs), in the outermost layer of diseased arteries. In a recent study, Mohanta, Habenicht, and colleagues revealed that there are distinct interactions between ATLOs and the autonomous nervous system, which are critically implicated in atherosclerosis progression.